Formação profissional e competência pedagógica: um estudo sobre o exercício da docência no SENAI-BA - Barbalho, Aylana Alves dos Santos Gazar (2009)
Society changes were the main focus of motivation of this research taking into account the productive context and the current demands of them, mainly deeming the competences and abilities that they are required to the contemporary worker. This research aimed to know and to analyze the profile and knowledge that integrate and are meaningful to the professionals' pedagogic practices that act as professors/teachers in formation process of the future worker at SENAI-Bahia. The research resulted in a analytic-describable diagnostic to approach topics about the formation and trajectory of the teachers of SENAI-BA, their social-cultural identity, their knowledge that mobilize in the teaching/learning process; its relevant curriculum, experience and professional knowledge. The investigation was accomplished in the beginning of the second semester of 2004 with teachers, course coordinators, pedagogic coordinators and students of the technical courses, Industrial learning modality, offered by 03 School of the SENAI-BA. As a result of the research, professionals of the most different areas, mainly of the Engineerings, when entering in SENAI and to assume, among other, the educational function, looked for several references to build his/her teaching practices. Regarding that the great majority of the teachers of SENAI-BA doesn't have pedagogic formation, they delineate and sustain their teaching practice based on their initial formation and their professional experience. However, they recognize their limitations, difficulties and certain insecurity, for not having the domain of the sciences that compose the complex structure of the education, as the basic foundation to the effective exercise of teaching.